Evaluation of Basal Serum Adrenocorticotropic Hormone and Cortisol Levels and Their Relationship with Nonalcoholic Fatty Liver Disease in Male Patients with Idiopathic Hypogonadotropic Hypogonadism - Wang, Wen-Bo; She, Fei; Xie, Li-Fang; Yan, Wen-Hua; Ouyang, Jin-Zhi; Wang, Bao-An; Ma, Hang-Yun; Zang, Li; Mu, Yi-Ming (Chinese medical journal, 2016)
Background： Prolonged gonadal hormone deficiency in patients with idiopathic hypogonadotropic hypogonadism （IHH） may produce adverse effects on the endocrine homeostasis and metabolism. This study aimed to compare basal serum adrenocorticotropic hormone （ACTH） and cortisol levels between male IHH patients and healthy controls. Moreover, this study compared the basal hypothalamic-pituitary-adrenal （HPA） axis in patients with and without nonalcoholic fatty liver disease （NAFLD）, and also evaluated the relationship between basal HPA axis and NAFLD in male IHH patients. Methods： This was a retrospective case-control study involving 75 Chinese male IHH patients （mean age 21.4 ± 3.8 years, range 17 30 years） and 135 healthy controls after matching tbr gender and age. All subjects underwent physical examination and blood testing for serum testosterone, luteinizing hormone, follicle-stimulating hormone. ACTH, and cortisol and biochemical tests. Results： Higher basal serum ACTH levels （8.25 ±3.78 pmol/L vs. 6.97 ±2.81 pmol/L） and lower cortisol levels （366.70 ±142.48 nmol/L vs. 452.82 ± 141.53 nmol/L） were observed ill male IHH patients than healthy subjects （all P 〈 0.05）. IHH patients also showed higher metabolism parameters and higher prevalence rate of NAFLD （34.9% vs. 4.4%） than the controls （all P 〈 0.05）. Basal serum ACTH （9.91 ±4.98 pmol/L vs. 7.60 ±2.96 pmol/L） and dehydroepiandrosterone sulfate （2123.7 ±925.8 μg/L vs. 1417.1 ±498.4 μg/L） levels were significantly higher in IHH patients with NAFLD than those without NAFLD （all P 〈 0.05）. We also found that basal serum ACTH levels were positively correlated with NAFLD （r = 0.289, P 〈 0.05） and triglyceride levels （r - 0.268, P 〈 0.05） in male IHH patients. Furthermore, NAFLD was independently associated with ACTH levels in male IHH patients by multiple linear regression analysis. Conclusions： The male IHH patients showed higher basal serum ACTH levels and lower cortisol levels than matched healthy controls. NAFLD was an independent associated factor for ACTH levels in male IHH patients. These preliminary findings provided evidence of the relationship between basal serum ACTH and NAFLD in male IHH patients.